Mortgage Valuation Under Optimal Prepayment - LeRoy, Stephen F. (Review of Financial Studies, 1996)
Mortgage originators offer borrowers various combinations of “points”—loan fees—and coupon: high points and low coupon or low points and high coupon. In this article points are interpreted as a device serving to separate borrowers with high prepayment probabilities from those with low prepayment probabilities. Borrowers and lenders are treated symmetrically: both are risk neutral and both have complete and frictionless access to credit markets (implying that borrowers can finance points if they wish), except that borrowers’ prepayment speeds are private knowledge. Equilibria are derived, both when borrowers cannot prepay voluntarily and when they can.